Finance Management Related Strategies Adopted by Households in Coping with Challenges of Economic Recession in Port Harcourt Local Government Area - C.U, Sonye; R. M, Kparevzua (Journal of Home Economics Research, 2024)
The study determined financial-management related strategies adopted by households during economic recession crisis as well as ways through which households can generate more income to cope with the challenges arising from economic recession. It was a survey research. Area of study was Port Harcourt Local Government Area (LGA). Population was made up of civil servants (both males and females). Questionnaire and focus group discussion (FGD) were used for data collection. Data were analyzed using mean. FGD information was also summarized. Major findings include 25 financial management strategies and 15 possible ways of generating more income. Based on the findings it was recommended among others that households should have an emergency fund savings, plan their budget, follow their budget strictly and have multiple source of income.